The influence of work-life balance, work motivation, and work environment on employee performance at PT. CNS Trading Indonesia, with organizational commitment as a mediating variable - Mohammad Wahyu Purnomo Adji; Batara Daniel Bagana (Universitas Nusa Cendana, 2026)
This study investigates the impacts of Work-Life Balance, Work Motivation, and Work Environment on Employee Performance, examining Organizational Commitment as a mediating factor at PT. CNS Trading Indonesia. Utilizing an associative quantitative framework, data were collected through online questionnaires from 74 purposively selected respondents. Analysis was conducted using Multiple Linear Regression and the Sobel Test. Findings reveal that Work Environment directly, positively, and significantly influences Employee Performance, whereas Work-Life Balance, Work Motivation, and Organizational Commitment show no direct significant effects. Regarding Organizational Commitment, Work Motivation and Work Environment demonstrate positive significant influences, while Work-Life Balance shows no significant effect. Additionally, the Sobel Test confirms that Organizational Commitment fails to mediate any relationships between the independent variables and Employee Performance. Consequently, PT. CNS Trading Indonesia's management should focus on enhancing physical and non-physical work environments to directly boost performance. Keywords: Work-Life Balance; Work Motivation; Work Environment; Organizational Commitment; Employee Performance